Implementasi Model Tilawati dalam Pembelajaran Al-Qur’an pada Anak Tunagrahita - Abdul Rochim; Mohammad Fahmi; M. Suyudi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The Qur'an is a guide for Muslims throughout the world, and they must learn it. Educating children to learn the Qur'an should begin as early as possible so that they can better grasp the Qur'an, with no exceptions for children with special needs, such as those with intellectual disabilities, who also have the right to academic and religious education. In general, there are still many children who cannot read the Qur'an. Therefore, this research aims to find out the implementation process, evaluation system, and implications of the application of the tilawati model in learning the Qur'an for children with intellectual disabilities at the Special School of the Foundation for the Development of Disabled Children (YPAC) Surabaya. This study employs a qualitative approach and descriptive method using a descriptive-qualitative research design. The research findings reveal that the process of integrating the tilawati paradigm in learning the Qur'an for children with intellectual disabilities at YPAC Surabaya Special School is carried out in one class with normal children, but is taught differently considering that learning for children with intellectual disabilities takes a long time. Regarding teaching methods, the learning process for these children is carried out by applying classical and individual methods.